Early onset of renal oxidative stress in small for gestational age newborn pigs - Hitesh Soni; Taisiya Yakimkova; Anberitha T. Matthews; Paul K. Amartey; Robert W. Read; Randal K. Buddington; Adebowale Adebiyi (Taylor & Francis Group, 2019)
Objective: Oxidative stress, a common feature in cardiovascular and renal disease is associated with the causes and consequences of fetal growth restriction. Hence, renal redox status is likely an early determinant of morbidity in small-for-gestational-age (SGA) infants. In this study, we examined renal oxidative stress in naturally-farrowed SGA newborn pigs. Methods: We studied SGA newborn pigs with 52% less body weight and 59% higher brain/liver weight ratio compared with their appropriate-for-gestational-age (AGA) counterparts. Results: The kidneys of the SGA newborn pigs weighed 56% less than the AGA group. The glomerular cross-sectional area was also smaller in the SGA group. SGA newborn pigs exhibited increased renal lipid peroxidation, reduced kidney and urine total antioxidant capacity, and increased renal nitrotyrosine immunostaining. Whereas the protein expression level of NADPH oxidase (NOX)2 was unchanged, NOX4 expression was significantly higher in SGA kidneys. The level of serum potassium was lower, but serum sodium and creatinine were similar in SGA compared with AGA newborn pigs. The serum concentrations of C‐reactive protein and NGAL, the biomarkers of inflammation and early acute kidney injury were significantly elevated in the SGA group. Conclusion: Early induction of oxidative stress may contribute to the onset of kidney injury in growth-restricted infants.